Energy from biomass and plastics recycling: a review. Issue 1 (1st January 2021) - Adegoke, Samuel Oluwafikayo; Adeleke, Adekunle Akanni; Ikubanni, Peter Pelumi; Nnodim, Chiebuka Timothy; Balogun, Ayokunle Olubusayo; Falode, Olugbenga Adebanjo; Adetona, Seun Olawumi
Abstract: The sustainability of fossil fuel is not guaranteed as it is gradually depleting. Alternative ways to this challenge are to generate biofuel from biomass and plastic solid wastes. Many studies have been done on the actualization of these alternatives. Hence, this study accumulates research from multidiscipline for the purpose of advancing biofuel production for sustainable energy. The necessary information needed by scientists having interest in biofuel production, including government policy, biomass selection, different conversion techniques and different ASTM standards for biodiesel properties are entrenched in this study. For vast biofuel production, there is a need for a collaborative work among fields from microbiologist, biochemist to engineering for the development of innovations, growth of cells, understanding of genetic engineering of algae strains and optimization of biofuel production. Also, a review on the recovery and recycling process of plastic solid waste was done. This is to ensure that the use of plastic solid waste to support energy sustenance will lead to no energy is wasted. Various ASTM standards for investigating the different properties of bio-oil were reviewed. The numerous plastic wastes that have not been utilized in the production of biofuel can be investigated to reduce the environmental pollution.